Profiling local-level outcomes of environmental decentralizations: the case of Cameroon’s forests in the Congo Basin - Oyono, P.R. (2005)
Since the mid-1990s, Cameroon has launched a process of decentralization of the management of its forests. Among other innovations, this decentralization process has transferred powers over forests and financial benefits accruing from their exploitation to local communities. This article explores and profiles its local-level outcomes. It shows that the experiment has not yet brought up expected positive results and very often generates internal conflicts, a new social stratification and the marginalization of traditional authorities. Second, the article argues that decentralized management is not producing positive economic results, as there is no significant economic change in the case study villages. Third, it demonstrates that the experiment is leading to negative environmental results, such as the degradation of many community forests in the forested Cameroon. It recommends that policy makers, researchers, nongovernmental organizations, and the local communities design a monitoring framework for decentralized management.